Social Norms and Unintended Effects in Audiovisual Gambling Prevention Campaigns - García Castro, Javier; Martínez , Luz; Cárdaba, Miguel Ángel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
Audiovisual public health campaigns on social media often use normative information to discourage unhealthy behaviors. While prescriptive norms suggest appropriate behavior, descriptive norms highlight the prevalence of undesirable actions. Research shows that descriptive norms can sometimes backfire, reinforcing the behaviors they aim to reduce (boomerang effect). However, their impact on gambling prevention remains underexplored. To address this gap, we conducted a systematic review using Web of Science, Scopus, Medline, and PsycInfo via EBSCO Discovery. This review examines how descriptive norms affect gambling prevention campaigns and provides evidence-based recommendations to enhance the effectiveness of gambling-related messaging